TURBULENCE IN COASTAL AND CIVIL ENGINEERING - Sumer, B. Mutlu, author 313158; Fuhrman, David R., author 643406 (Hackensack, NJ : World Scientific Publishing Co. Pte. Ltd., Singapore, 2020)
This book discusses the subject of turbulence encountered in coastal and civil engineering. The primary aim of the book is to describe turbulence processes including transition to turbulence; mean and fluctuating flows in channels/pipes, and in current and wave boundary layers; turbulence processes in breaking waves; and diffusion and dispersion processes in the coastal and river environment. Both phenomenological and statistical theories are described in great details. Turbulence modelling is also included, and together with several examples for modelling of turbulence in steady and wave boundary layers are presented. Readership: Graduate students and professionals in coastal and ocean engineering, focusing on turbulence.